Editor's Choice – Eligibility of Common Femoral Artery Atherosclerotic Disease for Endovascular Treatment – the CONFESS Study. (December 2022) - Kaneta, Gabriela; Husain, Shehzeen; Musto, Liam; Hamakarim, Tatiana; Elsharkawi, Ahmed; Littlejohn, Sofia; Helm, Jessica; Saratzis, Athanasios; Zayed, Hany
Abstract : Objective: Advances in endovascular technologies have allowed the treatment of common femoral artery (CFA) steno-occlusive disease by minimally invasive means; however, the proportion of lesions treated with common femoral artery endarterectomy (CFAE) which would be amenable to endovascular treatment is unknown. This observational study aimed to describe the morphology and composition of CFA lesions treated with CFAE and report the proportion that would be amenable to endovascular treatment with modern technologies. Methods: Patients presenting with symptomatic peripheral artery disease who underwent CFAE from January 2014 to December 2018 in two tertiary NHS hospitals were included. Extensive data relating to patient demographics, risk factors, clinical outcomes, as well as anatomical and morphological characteristics of the CFA atherosclerotic lesions, were collected which included detailed plaque analysis using 3D reconstruction of pre-operative computed tomography angiograms. CFA lesions were considered suitable for endovascular treatment if presented with patent iliac inflow, at least one patent outflow vessel (superficial femoral artery [SFA] or profunda femoral artery [PFA]), and stenotic rather than occluded CFA. Results: A total of 829 CFAs in 737 consecutive patients who underwent CFAE were included (mean age 71 ± 10 years; 526 males, 71%); 451 (62%) presented with chronic limb threatening ischaemia. Overall, 35% of CFAs had a localised lesion (no bifurcation disease) that could possibly be treated endovascularly. In total, 376 (45%) target vessels did not feature severe calcium load, with a patent CFA, PFA, and proximal SFA and therefore would have been amenable to endovascular treatment; while 271 CFAs (33%) featured a significant calcium load which would have potentially required stenting. Conclusion: A significant proportion of patients with atherosclerotic CFA lesions who undergo surgery could potentially be candidates for endovascular treatment. A randomised trial comparing CFAE and new endovascular techniques in this clinical context is required.